2019
DOI: 10.1080/0886022x.2019.1643737
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes aggravates renal ischemia and reperfusion injury in rats by exacerbating oxidative stress, inflammation, and apoptosis

Abstract: Diabetic patients are more susceptible to renal ischemia/reperfusion (I/R) injury (RI/RI) and have a poor prognosis, but the underlying mechanism remains unclear. The present study aimed to examine whether diabetes could worsen acute kidney injury induced by I/R in rats and clarify its mechanism. Control and streptozotocin-induced diabetic rats were subjected to 45 min renal pedicle occlusion followed by 24 h reperfusion. Tert-butylhydroquinone (TBHQ, 16.7 mg/kg) was administrated intraperitoneally 3 times at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 53 publications
3
37
0
Order By: Relevance
“…This was usually accompanied by the release of inflammatory cytokines, such as TNF-α, IL-1β and IL-6. Studies 4 , 24 showed that the inflammatory response induced by I/R injury was further exacerbated in diabetic rats, in which TNF-a and IL-1β levels in serum or renal tissues increased significantly. In this study, we have demonstrated that administration of resveratrol proved to be effective to inhibit the expression of the pro-inflammatory cytokines TNF-α and IL-1β elevated in the kidney of diabetic rats after I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…This was usually accompanied by the release of inflammatory cytokines, such as TNF-α, IL-1β and IL-6. Studies 4 , 24 showed that the inflammatory response induced by I/R injury was further exacerbated in diabetic rats, in which TNF-a and IL-1β levels in serum or renal tissues increased significantly. In this study, we have demonstrated that administration of resveratrol proved to be effective to inhibit the expression of the pro-inflammatory cytokines TNF-α and IL-1β elevated in the kidney of diabetic rats after I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia aggravates renal injury caused by I/R. Treatment with tert-butylhydroquinone (TBHQ) reduced I/R-related injury during diabetes via Nrf2 activation, reducing cell death and oxidative stress [ 132 ]. Exendin-4, a glucagon-like protein-1 (GLP-1) receptor agonist used in the treatment of diabetes, also activates Nrf2 leading to an increase in antioxidant and anti-inflammatory defenses.…”
Section: Nrf2 and Akimentioning
confidence: 99%
“…In vivo, treatment of tBHQ showed markedly cytoprotective effect in many tissues under pathological condition [17,18]. Administration of tBHQ could inhibit ROS generation and reduce renal injury in renal ischemia and reperfusion model [19]. Continuous tBHQ treatment markedly decreased and ameliorated proteinuria in type 1 diabetes mice [20].…”
Section: Discussionmentioning
confidence: 99%